If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + 3) + -5(x + -1) = 0 Reorder the terms: 2(3 + x) + -5(x + -1) = 0 (3 * 2 + x * 2) + -5(x + -1) = 0 (6 + 2x) + -5(x + -1) = 0 Reorder the terms: 6 + 2x + -5(-1 + x) = 0 6 + 2x + (-1 * -5 + x * -5) = 0 6 + 2x + (5 + -5x) = 0 Reorder the terms: 6 + 5 + 2x + -5x = 0 Combine like terms: 6 + 5 = 11 11 + 2x + -5x = 0 Combine like terms: 2x + -5x = -3x 11 + -3x = 0 Solving 11 + -3x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + -3x = 0 + -11 Combine like terms: 11 + -11 = 0 0 + -3x = 0 + -11 -3x = 0 + -11 Combine like terms: 0 + -11 = -11 -3x = -11 Divide each side by '-3'. x = 3.666666667 Simplifying x = 3.666666667
| 100=y-34 | | 2A(A-6)=0 | | 6(x+4)+5x=5(x+5)-7 | | 0.9p=5.4 | | 21=9a | | 2(X+3)-5(X+1)=0 | | b^2=21-10b | | x^2-12x-169=0 | | (X-0.5)*(X+2)=0 | | 2p=3p-5 | | 21+-1X+-1Y+5Y+20(1X+9)=351 | | (-2x^3+5x^2-x+7)+(4x^3-3x+2)= | | (8X-4)-(X+3)=0 | | 4a=-7a | | 5c+12=8c+10.23 | | -2x+4=x-6 | | 1(x+6)+4=7(x-2) | | (9A+7)+(5A-6)=0 | | 17x+3y=13 | | 10m^2+3m-21=0 | | q=1/3mr | | 21-2/7 | | X+y+1x+9=30 | | x+2y+4z=7 | | -3+5x-4+2x=-5x-5-9x | | -4(y+3)=4y-4+2(3y+1) | | 5n-3=2n-9 | | 72x=3 | | -4(-4w+2)-3w=3(w-3)-5 | | 2a+9d=47 | | 9=16+(-1r) | | t(8t+3)=0 |